Pengaruh Pendapatan Orang Tua dan Gaya Hidup Terhadap Pengelolaan Keuangan Mahasiswa Manajemen Universitas Singaperbangsa Karawang - Melinda; Irvan Yoga Pardistya (LPPM Universitas Buddhi Dharma, 2024)
This study aims to understand how students' parents' income and lifestyle influence their ability to manage personal finances. The focus of this research is students majoring in Management, considering that they are expected to have basic knowledge of financial management. This study uses a quantitative approach to collect data. The sample of students who were still actively receiving questionnaires was 65 students. The population in the study were Management students class 2021-2023 at the Faculty of Economics and Business. Using the Proportional Random Sampling method as a sampling method using data analyzed using the Multiple Regression Analysis test and t test and F test. From the results of the analysis, the author obtained the results of multiple linear regression analysis and obtained the equation Y = 9.673 + 0.490X1 + 0.034X2, which means that financial management (Y) is influenced by parents' income (X1) and lifestyle (X2). In synthesis, the results of the analysis show that every 1 unit increase in parental income will improve financial management by 0.490 units, while every 1 unit increase in lifestyle will increase financial management by 0.034 units. From the results of the t test, the influence of parental income on financial management is significant, with a significance level of 0.006 and a calculated t value of 2.863 which is greater than the critical value of 1.998. On the other hand, Lifestyle does not influence Financial Management, with a significance level of 0.829 which is greater than the general significance level and a calculated t value of 0.217 which is less than the critical value of 1.998. In the F Test results, the calculated f value was 5.338 which was greater than the table f value of 2.39. It is proven that H03 is rejected and H3 is accepted. Therefore, it is concluded that the influence of parental income (X1) and lifestyle (X2) has an influence on financial management (Y).